Beyond correlates: the social gradient in childhood overweight - Lina Hermeling; Jürgen M. Steinacker; Susanne Kobel (BMC, 2024)
Abstract Background Health (in)equity has a high priority on research and policy agendas. Even though it is known that inequalities in overweight prevalence accumulate with age and are already existent among children below the age of six, research on this topic is scarce. In this young age group, parents play an important role in preventing overweight and associated adverse consequences. This study examines the magnitude of parental misclassification of child weight status and its correlates, focussing on the factors that determine social status and equity. Methods Preschool children's weight and height was measured objectively. Parents gave information on their socioeconomic background. Family education was dichotomised into tertiary and non-tertiary educational level, according to CASMIN. Binary logistic regression, adjusted for parental BMI, was applied to detect odds of childhood overweight. Results Data on family educational level and anthropometrics were available from 643 children (4.5 ± 0.82 years, 52.7% male) and their parents of which 46.5% (n = 299) had a tertiary educational background. The groups (tertiary vs. non-tertiary educational level) differ significantly in overweight prevalence (3.7% vs. 11.9%, p ≤ 0.001). Odds of overweight were two times higher in children with non-tertiary educational background (OR: 2.123, CI: 1.010-4.461, p < 0.05), adjusted for parental BMI. Conclusion Children from families with low educational background have an elevated risk of overweight, already at a very young age. Education in general (not explicitly health education) seems to play a tremendous role in the prevention of overweight and obesity and should therefore be implied in policies enhancing health equity. Trial registration DRKS-ID: DRKS00010089.